Deciphering variable resistance to novel carbapenem-based β-lactamase inhibitor combinations in a multi-clonal outbreak caused by Klebsiella pneumoniae carbapenemase (KPC)-producing Klebsiella pneumoniae resistant to ceftazidime/avibactam. (April 2023) - Di Pilato, Vincenzo; Principe, Luigi; Andriani, Lilia; Aiezza, Noemi; Coppi, Marco; Ricci, Silvia; Giani, Tommaso; Luzzaro, Francesco; Rossolini, Gian Maria
Abstract: Objectives: Carbapenemase-producing Enterobacterales represent a major cause of difficult-to-treat infections world-wide. Novel β-lactam/β-lactamase inhibitor combinations, including ceftazidime/avibactam (CZA), meropenem/vaborbactam (MVB), and imipenem/relebactam (IMR), represented a break-through in the treatment of some carbapenemase-producing Enterobacterales infections. However, acquired resistance to these agents has been reported in Klebsiella pneumoniae carbapenemase (KPC)-producing Enterobacterales . Herein, we reported an outbreak caused by CZA-resistant, KPC-producing Klebsiella pneumoniae (KPC-Kp), which was also variably resistant to carbapenem-based β-lactam/β-lactamase inhibitor combinations. Methods: Bacterial isolates were subjected to antimicrobial susceptibility testing, whole-genome sequencing, determination of bla KPC gene dosage, and analysis of carbapenemase activity. Results: Overall, 15 KPC-Kp, nine CZA-resistant (CZA R ), and six CZA-susceptible isolates were collected from an outbreak involving six patients in a neurorehabilitation facility. Of the nine CZA R isolates, seven were also resistant to MVB and one was also resistant to IMR. Whole-genome sequencing revealed that the outbreak was multi-clonal, with CZA R KPC-Kp belonging to the ST101, ST1519, and two ST512 sub-lineages, which were involved in two independent transmission clusters. Resistance to CZA was primarily mediated by overproduction of KPC-3 associated with increased gene dosage, a mechanism accounting for cross-resistance to MVB in most cases, and to IMR in a single KPC-Kp isolate; multiple OmpK36 aletarions were also detected. Mutated KPC (KPC-53) was detected in a single case. Positivity for CZA R KPC-Kp was inconstantly associated with previous CZA exposure. Conclusions: In this multi-clonal outbreak of KPC-Kp, the overproduction of KPC-3 was the leading mechanism of cross-resistance to CZA and MVB, whereas resistance to IMR appeared less affected. The emergence and dissemination of similar resistance mechanisms may have relevant clinical and diagnostic implications, and their surveillance is warranted.